Fusion of CtxB with StxB, Cloning and Expression of in Esherichia coli: A challenge for Improvement of Immune Response Against StxB: Cloning and coexpression of ctB-stxB fusion in E. coli - Hamid Madanchi; Hossein Honari; Mohammad Sadraeian; Mahdi Hesaraki (Iranian Journal of Pharmaceutical Sciences, 2011)
Cholera toxin B subunit (CtxB) is a homopantameric, nontoxic subunit of cholera toxin that is responsible for its binding to the cell and has been known as a mucosal adjuvant for vaccines that could increase homoral and mocusal immunity response. In this work, the CtxB gene was fused to the StxB gene from Shigella dysenteriae type I a vaccine antigen candidate against this pathogen, by a nonfurin linker then ligated with pGEM vector and subcloned in the pET28a(+) as an expression vector . The CtxB-StxB fusion protein was expressed in Escherichia coli, and purified by a Ni-NTA resin column, then detected molecular weight and immunogenicity by SDS-PAGE and Western-blot. StxB has low molecular weight, so immune response against it is low, while CtxB is a potent mucosal adjuvant. In this method, the CtxB-StxB fusion protein was expressed in Escherichia coli in order to use its natural adjuvanticity of the CtxB which will enhance immune response against StxB, as well as, it will produce immune response against both shiga and cholera toxins.